Economics of broiler fattening in Hungary - Szőllősi, László (Acta Agraria Debreceniensis, 2008)
The purpose of this study is to present economic circumstances of Hungarian broiler sector based on secondary data after brief introduction of international and home situations. Then it analyzes costs, revenues and profit relationships of producers, which has competitive efficiency indicators and high standard production based on a model created on the basis of primary data. The paper confirms the Hungarian poultry sector international competitiveness falling. One important reason of this situation is the low profitability in the sector, which is typical of both farms produce under worse efficiency indicators and high standard producers. Beside lack of technological standards and efficiency, adverse trend of output and input price – mainly feed price – impact low profitability. Realization of technological developments and improvements according to international tendency, which affect directly or indirectly the efficiency and costs of broiler fattening are determining in point of realizable profit